Evaluating Fractional PID Control in a Nonlinear MIMO Model of a Hydroelectric Power Station - O. A. Rosas-Jaimes; G. A. Munoz-Hernandez; G. Mino-Aguilar; J. Castaneda-Camacho; C. A. Gracios-Marin (Complexity)
In this paper a Fractional PID Control is presented. This control was designed for a hydropower plant with six generation units working in an alternation scheme. The parameters and other features of such a set of hydrogeneration units have been used to perform the respective tuning up. In order to assess the behavior of this controlled system, a model of such nonlinear plant is regulated through a classical PID by classical linearization of its set points, and then a pseudo-derivative part is substituted into a Fractional PID. Both groups of signals contain variations of voltage suggesting some abrupt changes in the supply of electricity fed to the network. Both sets of resulting signals are compared; the simulations show that the Fractional PID has a faster response with respect to those plots obtained from the classical PID used.